A comprehensive description and range extension of the formerly Bolivian endemic Clematis uruboensis (Ranunculaceae) to Brazil - Piovesani, Willian Souza; Ferreira, Priscila Porto Alegre; Seger, Guilherme Dubal Dos Santos (Phytotaxa, 2025)
In this study, we complement the original description of Clematis uruboensis (Ranunculacaee) by analyzing specimens with pistillate, staminate flowers, and fruits, and we extend the distribution range of this species, previously considered endemic to Bolivia, into Brazil. We identified eight new records for Brazil and six for Bolivia. Furthermore, we provide a preliminary extinction risk assessment of the species.